Genetics International Student Version - Snustad, D. Peter Simmons, Michael J (John Wiley & Sons, 2012)
Snustad's 6 th edition of Principles of Genetics offers many new and advanced features including boxed sections with the latest advances in Genetics, a streamlined roster of topics, a more reader-friendly layout, and new problem-solving supplements.